A new synonym of Sericothrips from China and Japan (Thysanoptera: Thripidae) - Mirab-Balou, Majid; Minoura, Kazushige; Tong, Xiao-Li (Zootaxa, 2013)
Nine species are listed in the genus Sericothrips (Thripidae: Sericothripinae) (Mound 2013), and all of these species have the abdominal tergites completely covered with microtrichia medially (Mound & Tree 2009). S. marginalis Kudô was described from Japan on a large number of specimens, including a micropterous holotype and macropterous females and micropterous males. These specimens were collected from plants in the families Poaceae and Fabaceae (Kudô 1991). Specimens from Japan were examined by the first author (including one paratype in SCAU), and three paratypes were also checked by the second author and compared with Chinese specimens of S. houji (Chou & Feng 1990). We were not able to find any character differences between these two species, and therefore place S. marginalis in synonymy with S. houji.